Plasmacytoid urothelial carcinoma with duodenal metastasis-A rare tumor with unusual site of metastasis with grim outcome - Aparna Chenniappan; Norton S Stephen; Bheemanathi H Srinivas; Sreerag K Sreenivasan; Ramkumar Govindarajalou (Wolters Kluwer Medknow Publications, 2024)
Plasmacytoid urothelial carcinoma (PUC) is a newly recognized rare variant of urothelial carcinoma, which is now being increasingly diagnosed prospectively as well as by retrospective analysis of cases with a poor prognosis. Morphologically, these tumors simulate plasma cell neoplasms and pose a diagnostic challenge. Identifying this variant is essential in two aspects: therapy and prognosis. Here, we present a case who underwent multiple transurethral resection of bladder tumor (TURBT) procedures, each with a diagnosis of urothelial carcinoma, the plasmacytoid type which was confirmed on radical cystectomy, and after 1 year, the patient presented with duodenal metastasis. We discuss the morphological aspects of differentiating this tumor from variants of urothelial carcinoma and other tumors with a plasmacytoid appearance. Despite the recognition and aggressive treatment, the patient expires within 2 years of the first diagnosis of bladder carcinoma.